1991
DOI: 10.1111/j.1365-2044.1991.tb09843.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response relationship and time course of action of Org 9426

Abstract: SummaryOrg 9426 is a new nondepolarising neuromuscular blocking agent with a chemical structure related to that of vecuronium, as shown in Figure 1.From recent clinical studies Org 9426 appeared to be five to seven times less potent than vecuronium and showed a faster rate of onset of neuromuscular block [I, 21, whereas duration of action and recovery index were found to be similar [2]. Good to excellent intubation conditions were shown within 60 s after approximately 1.5 times the ED,,, dose [2]. Org 9426, av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…These resuts are in accordance with those of other recent studies [5,12,[20][21][22], which showed no significant differences in the onset times of rocuronium under volatile anesthetics. In our study, the shortest onset time (90.67 s) was observed in the sevoflurane group.…”
Section: Resultssupporting
confidence: 95%
“…These resuts are in accordance with those of other recent studies [5,12,[20][21][22], which showed no significant differences in the onset times of rocuronium under volatile anesthetics. In our study, the shortest onset time (90.67 s) was observed in the sevoflurane group.…”
Section: Resultssupporting
confidence: 95%
“…Both groups of patients had median onset times of 4-5 min and a depth of block of 85-90% after 0.3 mg kg Ϫ1 rocuronium. These are similar to values found in previous studies [6] where mechanomyograph recordings were used. Eriksson in an Editorial in Anesthesiology has suggested that it is time that quantitative assessment of neuromuscular block be routine, or even mandatory, when non-depolarizing neuromuscular blocking agents are used [7].…”
Section: Discussionsupporting
confidence: 71%
“…They concluded that intravenous anaesthetics do not appear to interact with rocuronium to a clinical significant degree. Lambalk et al [18] concluded that the influence of different anaesthetics on the time course of rocuronium was only fractional. We did not monitor neuromuscular function in our patients because of anticipated discomfort with baseline nerve stimulation in the awake state.…”
mentioning
confidence: 99%